THE RESEARCH OF OPERATOR'S CEREBRAL INTERHEMISPHERIC ASYMMETRY DURING THE MONOTONOUS WORK ON THE COMPUTER (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
It is revealed that during the operator's monotonous work cerebral hemispheres take part in the stages of information processing in certain order: the right hemisphere realizes receiving and processing stages and the left hemisphere – late cognitive processes.